Comparing Designers' Behavior in Responding to Unexpected Discoveries in Parametric Design Environments and Geometry Modeling Environments. (December 2013) - Yu, Rongrong; Gu, Ning; Lee, Ju Hyun
This paper presents a protocol study which compares designers' behaviors when unexpected discoveries appear in a parametric design environment (PDE) and a traditional geometry modeling environment (GME). From the view of design situatedness, designers tend to adapt and respond to the design situation as it continuously changes during the design process. The hypothesis is that when unexpected discoveries appear, these changing design situations can significantly affect designers' cognitive activities. In this study, we are interested in exploring designers' behaviors in responding to these unexpected discoveries in PDEs, and further, to compare those behaviors in GMEs. An experiment was conducted in which five designers completed two similar design tasks respectively in a PDE and a GME. Applying the research method of protocol analysis, designers' behaviors in response to unexpected discoveries in these two design environments are compared and discussed.